Measuring the Effectiveness of Direct General Elections as a Means of Democracy in Regional Head Elections - Muhammad Halim; Zudan Arief Fakrulloh (Jurnal Multidisiplin Indonesia, 2025)
Direct regional head elections are one of the real manifestations of democracy at the local level in Indonesia. Through this system, the community is given full rights to elect their leaders directly, without intermediaries, as a form of essential political participation. This study aims to measure the effectiveness of direct elections as a means of democracy by examining the extent to which this mechanism can create quality regional leadership, accountable, and responsive to the people's aspirations. In addition, an analysis was carried out on various challenges faced in its implementation, such as the practice of money politics, low political literacy, and the dominance of party elites. The findings show that although direct elections open up wider space for public participation, their effectiveness still depends on the quality of the organizing institutions, the regulations that govern them, and the political awareness of the community.